Recurrent acral ulcerations associated with DNA methyltransferase 1-complex disorder - Cerejeira,Diogo (2022)
Abstract DNA methyltransferase 1, encoded by DNMT gene, is a crucial DNA methyltransferase with essential roles in transcription regulation, gene imprinting, and cell differentiation. Dysfunction of this group of enzymes can lead to a variety of neurologically predominant clinical symptoms, including a stereotypic triad of sensory predominant neuropathy, sensorineural hearing loss, and cognitive decline. Herein, we report the case of a Portuguese patient who presented with recurrent acral ulcerations due to hypoalgesia and hypoesthesia, secondary to a novel heterozygous mutation [c.1718T>G (p.Val573Gly)] in DNA methyltransferase 1 gene.